Environmental factor as predictors of citizens’ participation in development activities in Ogbomoso town, Oyo state, Nigeria (2023)
The involvement of citizens in developmental endeavors is crucial to achieving rapid and enduring progress. However, the social context often displays varying attitudes that impact community participation. Despite numerous studies on citizen engagement, there is a shortage of research on how different environmental factors influence involvement in community development. This study, investigated the environmental factors that could predict citizens’ participation in developmental activities in Ogbomoso, Oyo State. The descriptive survey research design was adopted. The simple random sampling was used to select 100 respondents from the community of Ogbomoso North Local Government. The data was analysed using the descriptive statistics of percentage, frequency count and inferential statistics of multiple regression. Environmental factors (leadership impact and involvement in community groups) jointly influenced citizens’ participation in development activities (R = 0.46, p<0.05). These factors accounted for 0.20% of the total variance in citizens’ participation in development activities. The relative contribution of the variables is as follows; Leadership impact (β= 0.36; t = 3.59; p < 0.05) and Involvement in community groups ((β= 0.17; t = -1.68; p >0.05). The result showed that citizens participate in development activities irrespective of their involvement in community groups and leadership greatly influences citizens’ participation in developmental activities. Since leadership determines peoples’ participation in community development projects, it is recommended that community leaders should be exemplary in discharging their duties and also visualise projects that are need-based